Interview with political leaders / Ilias Md. Salleh - Md. Salleh, Ilias (Faculty of Communication and Media Studies (FCMS), 1994)
A survey was conducted in several electoral constituencies predetermined earlier to gauge the opinions of political leaders regarding the role of media in the 1990 general elections.